Manufacturers' Expenses, Net Production, and Rigid Costs in Canada - MacGregor, Donald C. (The Review of Economics and Statistics, 1945)
TWO surveys of the operating expenses of Canadian manufacturers have been made in the last twenty-five years. The fLrst covers all establishments reporting to the Dominion Bureau of Statistics for the Census of Manufactures in each of the five years I9I 7 to 192 I; the second, undertaken for the Royal Commission on Dominion-Provincial Relations in I938, covers in greater detail a limited but fairly representative group of manufacturers for each of the years I929, I933, and I936. The present paper describes the origin, methods, and results of the second or I938 survey, and provides a summary of the I9I7-2I study. In addition, it attempts to arrange the results of both surveys in comparable form.' Because of the difficulty of securing reliable figures by the method employed in the I938 survey, special attention is given to the representativeness of the results. Certain details of importance for the text will be found in appendices. Among the tables presented, Table 9 is of most general interest, while certain applications of the results will be found in Tables io and i i.